Antioxidant Potential, Antidiabetic, and Anti-Inflammatory Activities of White Cowpea (Vigna unguiculata L.): An in vitro Study - Priyadarshini, R. Durga; Beatrice, D. Annette; Sivaraj, C. (Asian Journal of Biological and Life Sciences)
Aim/Background: Legumes are nutrient-dense with bioactive compounds offering protective effects against non-communicable diseases. The study aimed to screen phytochemicals, determine the total phenol and flavonoid contents and assess the in vitro antioxidant potential, and antidiabetic and anti-inflammatory activity of white cowpeas. Materials and Methods: Aqueous and ethanolic extracts of white cowpea were prepared. Total phenol content was estimated using the Folin- Ciocalteu colorimetric method and total flavonoid content was estimated using the aluminium chloride method. The antioxidant potential was assessed using DPPH assay, superoxide radical scavenging assay, phosphomolybdenum reduction assay and FRAP assay. The antidiabetic activity was evaluated using an alpha-amylase inhibition assay and the anti-inflammatory activity was evaluated using a human red blood cells membrane stabilization assay. Results: The total phenolic and total flavonoid content of white cowpea was two folds higher in the ethanol extract (343.67±1.19 μg/mg GAE and 60.87±0.33 μg/mg QE, respectively) than aqueous extract. Antioxidant analysis revealed that the ethanol extract exerted superior activity with an IC50 of 47.21±0.09 μg/mL against DPPH, 110.6±0.2 μg/mL against superoxide anions, 49.62±0.26 μg/ mL against ferric while the aqueous extract had superior activity against phosphomolybdenum with an IC50 of 30.05±0.02 μg/mL. The anti-diabetic and anti-inflammatory analysis revealed superior activity of ethanol extract (30.88±0.51 μg/mL; 97.99±3.34 μg/mL, respectively) on par with the standard (acarbose and aspirin, respectively). The principal bioactive compounds present in white cowpea are ethyl α-d-glucopyranoside (43.24%), melezitose (18.25%) and 3-O-Methyl-d-glucose (11.19%). Conclusion: White cowpeas are rich in bioactive compounds with excellent antioxidant potential, anti-diabetic and anti-inflammatory activity.
Keywords: Anti-inflammatory; Antidiabetic; Antioxidant; White Cowpea